2018
DOI: 10.1002/ece3.3755
|View full text |Cite
|
Sign up to set email alerts
|

The strength of negative plant–soil feedback increases from the intraspecific to the interspecific and the functional group level

Abstract: One of the processes that may play a key role in plant species coexistence and ecosystem functioning is plant–soil feedback, the effect of plants on associated soil communities and the resulting feedback on plant performance. Plant–soil feedback at the interspecific level (comparing growth on own soil with growth on soil from different species) has been studied extensively, while plant–soil feedback at the intraspecific level (comparing growth on own soil with growth on soil from different accessions within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
(110 reference statements)
3
22
0
Order By: Relevance
“…Therefore, the ultimate response of plants to their neighbors depends on the complex interplay of mechanisms that integrate numerous environmental cues in which root exudates are undoubtedly involved. Recent studies have shown how plant-soil feedbacks, mostly determined by the relationship between the plant and the soil microbial community, can determine plant performance and community structure (Kardol et al., 2007; Reinhart, 2012; Ma et al., 2017; Van Nuland et al., 2017; Bukowski et al., 2018; Eppinga et al., 2018; Hu et al., 2018; Wubs and Bezemer, 2018). Indeed, in recent experiments, it was shown that effects on plant performance by soil microbiota through plant-soil feedbacks were dependent on the plant nutrient strategy and soil nutrient conditions (Png et al., 2019; Teste et al., 2017).…”
Section: Implications At the Ecosystem Scalementioning
confidence: 99%
“…Therefore, the ultimate response of plants to their neighbors depends on the complex interplay of mechanisms that integrate numerous environmental cues in which root exudates are undoubtedly involved. Recent studies have shown how plant-soil feedbacks, mostly determined by the relationship between the plant and the soil microbial community, can determine plant performance and community structure (Kardol et al., 2007; Reinhart, 2012; Ma et al., 2017; Van Nuland et al., 2017; Bukowski et al., 2018; Eppinga et al., 2018; Hu et al., 2018; Wubs and Bezemer, 2018). Indeed, in recent experiments, it was shown that effects on plant performance by soil microbiota through plant-soil feedbacks were dependent on the plant nutrient strategy and soil nutrient conditions (Png et al., 2019; Teste et al., 2017).…”
Section: Implications At the Ecosystem Scalementioning
confidence: 99%
“…Plant-soil feedback experimental design We followed a common methodology for plant-soil feedback experiments (Fig. 1), consisting of two phases: a conditioning phase (phase 1) and a feedback phase (phase 2) (Bever 2003;Bukowski et al 2018;Kulmatiski and Kadrol 2008). Plants were grown under well-watered conditions for all treatments throughout both the conditioning and feedback phases to speci cally assess the legacy effects of past rainfall regime (i.e.…”
Section: Soil Origin and Plant Speciesmentioning
confidence: 99%
“…, Bukowski et al. ). Biological invasions are often characterized by multiple introduction events, meaning multiple genetic lineages may be present in the introduced range (Durka et al.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, intraspecific genetic variation is an important part of ecological and evolutionary processes (see Bolnick et al 2011 for a review). It is known to alter the effects of nutrients (Saltonstall and Stevenson 2007) and competitors (Howard et al 2008, Gomola et al 2017) on plant fitness, and to influence community composition of soil biota (Schweitzer et al 2008, Nelson and Karp 2013, Lamit et al 2016, Bowen et al 2017), yet experiments examining intraspecific variation in PSFs remain rare (but see Bukowski and Petermann 2014, Maron et al 2015, Wagg et al 2015, Bukowski et al 2018. Biological invasions are often characterized by multiple introduction events, meaning multiple genetic lineages may be present in the introduced range (Durka et al 2005, Meyerson et al 2012, Gomola et al 2017.…”
Section: Introductionmentioning
confidence: 99%